2011
DOI: 10.1523/jneurosci.6538-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivity in the Ventral Cochlear Nucleus after Cochlear Trauma

Abstract: The emergence of hyperactivity in the form of elevated spontaneous firing rates after cochlear trauma has been well documented in a number of central auditory structures, including the auditory cortex, inferior colliculus, and dorsal subdivision of the cochlear nucleus. This hyperactivity is of interest as a possible neural substrate of tinnitus. Whether the ventral subdivision of the cochlear nucleus shows hyperactivity has never been investigated despite the fact that, like the dorsal division, it also recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 44 publications
4
104
2
Order By: Relevance
“…Recent neurophysiological data in animals supports the presence of increased SBC excitability following acoustic trauma, a common cause of tinnitus (Vogler et al 2011). In particular, elevated spontaneous activity was evident in the VCN, particularly in two VCN unit types, one of which (primary-like) corresponds to SBCs.…”
Section: Ventral Cochlear Nucleus and Tinnitusmentioning
confidence: 91%
“…Recent neurophysiological data in animals supports the presence of increased SBC excitability following acoustic trauma, a common cause of tinnitus (Vogler et al 2011). In particular, elevated spontaneous activity was evident in the VCN, particularly in two VCN unit types, one of which (primary-like) corresponds to SBCs.…”
Section: Ventral Cochlear Nucleus and Tinnitusmentioning
confidence: 91%
“…5). Electrophysiological studies of the VCN have confirmed significant increases in spontaneous activity after acoustic trauma or mechanical lesions of the cochlea (Vogler et al 2011). Unit classifications based on the shape of peri-stimulus time histograms (PSTHs) linked the largest rate increases to primary-like units, which represent the physiological counterpart of SBCs.…”
Section: Role Of the Vcnmentioning
confidence: 99%
“…In the context of existing neurophysiological models, DCN-based hyperactivity is expected to target type O units (Kaltenbach 2006;Robertson et al 2013). Conversely, VCN-based hyperactivity is directed toward type V and I units (Vogler et al 2011).…”
Section: Surgical Preparation and Single-unit Recordingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is partially explained by considering that ABR thresholds (āˆ¼30 dB SPL) are significantly higher than single-fiber thresholds (āˆ¼0 dB SPL (Taberner and Liberman, 2005)); thus, an additional 10 dB increase to āˆ¼40 dB SPL by impinging on the more broadly tuned portions of ANF tuning curves, rapidly recruits ANFs over large extents of the cochlear spiral. For ABRs, another contributing factor is that a peripheral neuropathy may enhance responses in the central auditory nuclei, such as cochlear nucleus and the inferior colliculus (Mulders and Robertson, 2009;Vogler et al, 2011), which contribute to the later waves that typically appear at lower SPLs than wave 1. Indeed, post-exposure decreases in ABR thresholds, without parallel changes in DPOAE thresholds, have been noted in the acoustic trauma model of neuropathy (Fig.…”
Section: Abrs and The Quantitative Assessment Of Cochlear Neuropathymentioning
confidence: 99%